Structure of surfaces and interfaces of poly(N,N-dimethylacrylamide) hydrogels - Sudre, Guillaume (Langmuir : the ACS journal of surfaces and colloids, 2012)
We investigated the surface structure of hydrogels of poly(N,N-dimethylacrylamide) (PDMA) hydrogels synthesized and cross-linked simultaneously by redox free radical polymerization. We demonstrate the existence of a less cross-linked layer at the surface of the gel at least at two different length scales characterized by shear rheology and by neutron reflectivity, suggesting the existence of a gradient in cross-linking. The composition of the layer is shown to depend on the degree of hydrophobicity of the mold surface and is weaker for more hydrophobic molds. While the macroscopic tests proved the existence of a relatively thick under-cross-linked layer, we also demonstrated by neutron reflectivity that the gel surface at the submicrometric scale (500 nm) was also affected by the surface treatment of the mold. These results should have important implications for the measurement of macroscopic surface properties of these hydrogels such as friction or adhesion